Intraoperative indocyanine green fluorescence navigation in a robot-assisted partial nephrectomy for a large renal cell carcinoma in a horseshoe kidney. Issue 6 (20th June 2022) - Holmes, Angela; Tissot, Sophie; O'Neill, Sarah; Kearns, Paul
Abstract : A man in his 60s was referred to the urology department with an incidental finding of large 75 mm mass within a horseshoe kidney. CT imaging highlighted the well-known aberrant arterial anatomy seen in horseshoe kidney which often causes significant surgical challenges. After careful preoperative planning, the mass was resected successfully during a robot-assisted partial nephrectomy. Intraoperatively, indocyanine green fluorescence navigation helped to confirm arteries supplying area of resection were appropriately clamped, allowing for safe resection of the mass. Histology revealed a chromophobe renal cell carcinoma with clear margins. The patient was discharged on day 4 postoperatively and continues to be cancer free on routine surveillance imaging.